Whole-genome analysis of Bacillus paranthracis YC06 isolated from healthy individual feces for biodegrading inosine and guanosine - Xiaoyu Cao; Yu Zhang; Qianqian Xu; Hai Yan (BMC Microbiology)
Abstract The overproduction of uric acid, driven by its key precursors (inosine and guanosine), leads to hyperuricemia, a metabolic disorder associated with severe complications such as gout and renal dysfunction. Here, a promising bacterial strain YC06 with excellent biodegradation capability for inosine and guanosine was successfully isolated from healthy individual feces and identified as Bacillus paranthracis through average nucleotide identity (ANI) analysis. B. paranthracis YC06 resting cells (live but suspended in PBS buffer) and its cell-free extracts could effectively biodegrade inosine and guanosine in vitro. Whole-genome sequencing revealed a 5,535,183 bp draft genome (52 contigs, 35.22% GC content) containing 5,672 protein-coding genes. B. paranthracis YC06 demonstrated high survival rates in simulated gastrointestinal fluids, supported by the presence of stress-response genes and bile salt hydrolase genes associated with gastrointestinal tolerance. However, this strain exhibited hemolytic activity and no amino acid decarboxylase activity, while hemolysin genes, antibiotic genes and toxin-producing genes were identified, raising potential biosafety concerns for its further application. The gene functional annotation and polymerase chain reaction (PCR) amplification electrophoresis identified key genes (rihA, rihB, deoD and pnp) encoding purine nucleosidase and purine-nucleoside phosphorylase, and combined with biodegradation product analysis, elucidated the pathways of inosine and guanosine biodegradation into hypoxanthine and guanine. Comprehensive safety evaluations, including cytotoxicity assay and in vivo pathogenicity studies, must be conducted to rigorously assess its risks prior to practical utilization.